2023
DOI: 10.1200/jco.21.02303
|View full text |Cite
|
Sign up to set email alerts
|

FORT-1: Phase II/III Study of Rogaratinib Versus Chemotherapy in Patients With Locally Advanced or Metastatic Urothelial Carcinoma Selected Based on FGFR1/3 mRNA Expression

Abstract: PURPOSE Rogaratinib, an oral pan-fibroblast growth factor receptor (FGFR1-4) inhibitor, showed promising phase I efficacy and safety in patients with advanced urothelial carcinoma (UC) with FGFR1-3 mRNA overexpression. We assessed rogaratinib efficacy and safety versus chemotherapy in patients with FGFR mRNA-positive advanced/metastatic UC previously treated with platinum chemotherapy. METHODS FORT-1 (ClinicalTrials.gov identifier: NCT03410693 ) was a phase II/III, randomized, open-label trial. Patients with F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Common adverse effects include diarrhea, decreased appetite, fatigue, and asymptomatic lipase elevation. 370 , 371 E7090 selectively inhibits FGFR1–3 and has been found to be effective in patients with cholangiocarcinoma with FGFR2 gene fusions and in patients with gastric cancer with FGFR2 gene amplification or increased expression, but more information is needed for a larger sample size. 372 Debio 1347 is an ATP‐competitive, highly selective FGFR1–3 inhibitor, and it is mainly used to treat breast cancer and cholangiocarcinoma.…”
Section: Fgfr Acts As a Therapeutic Targetmentioning
confidence: 99%
“…Common adverse effects include diarrhea, decreased appetite, fatigue, and asymptomatic lipase elevation. 370 , 371 E7090 selectively inhibits FGFR1–3 and has been found to be effective in patients with cholangiocarcinoma with FGFR2 gene fusions and in patients with gastric cancer with FGFR2 gene amplification or increased expression, but more information is needed for a larger sample size. 372 Debio 1347 is an ATP‐competitive, highly selective FGFR1–3 inhibitor, and it is mainly used to treat breast cancer and cholangiocarcinoma.…”
Section: Fgfr Acts As a Therapeutic Targetmentioning
confidence: 99%
“…Rogaratinib development provides a recent example. Although this drug was evaluated in patients selected according to FGFR 1-3 mRNA expression levels, in the FORT-1 study, testing rogaratinib monotherapy against investigator-choice chemotherapy as second-line therapy, the ORR increased from 20.7% to 52.4% in patients also harboring a FGFR3 GA ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of FGFRs has been implicated in various human malignancies, including UC, in which genetic alterations of FGFR1-3 have been implicated (17). Recent research on molecular subtypes and ICIs therapy has shown that UC of the bladder with FGFR3 mutation or high expression has a comparatively low immune signature and lower expression of PD-L1 (18,19). Inhibition of FGFR3 in FGFR3-activated bladder cancer has been shown to increase PD-L1 protein levels by changing its ubiquitination, which in turn regulates CD8+ T cells from engaging in antitumor activity (20).…”
Section: Discussionmentioning
confidence: 99%